(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the context of information abundance characteristic of the digital age, media education and libraries play a key role in the development of media literacy among the population. By interacting with each other, they help people not only find the necessary information but also critically evaluate it, use it wisely, and create their own content, transforming libraries into modern centers of knowledge and learning.Media education is a field of education that focuses on the study and use of various types of media for learning purposes. In the context of modern information realities, the training of library specialists is unthinkable without the development of deep media literacy.The set of competencies that make up the content of media and information literacy enables future specialists to operate effectively in the information space and provide high-quality library services. The aim of the study is to systematize theoretical knowledge and empirical data in the process of developing media literacy among library specialists in order to identify the most effective methods and strategies for enhancing their media competence.The proposed methods include interactive learning, project-based learning, collaborative learning, the use of digital technologies, modeling real work situations, critical analysis of media content, and scientific research activities. The essence of these methods lies in developing specialists’ ability to work effectively in the modern information space, critically evaluate media content, use digital technologies, and educate users.